THE EFFECTIVENESS OF USING AUDIOVISUAL MEDIA IN LEARNING TO WRITE INDONESIAN DRAMA SCRIPT - Djumingin, Sulastriningsih; Juanda,; Azis, (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
This research aims to prove the effectiveness of using audiovisual media in learning to write drama scripts for students. The population in this research were students of class XII Social Science which collected 90 people from three classes. The sample was determined by purposive sampling technique in order to obtain 2 classes as the experimental and control classes. The research design was a quasi-experimental. The instrument used is a drama writing test. The collected data were analyzed using descriptive analysis and inferential analysis in the form of independent t-test. The results showed that the group using audiovisual media obtained better results than audio media. The results of the study were evidenced by a t-test which showed that audiovisual media was effectively used in learning to write drama scripts. The implication of this research is that teachers can improve students' ability to write Indonesian drama scripts using audiovisual media. Abstrak: Penelitian ini bertujuan untuk membuktikan keefektifan penggunaan media audiovisual dalam pembelajaran menulis naskah drama siswa. Populasi dalam penelitian ini adalah siswa kelas XII IPS yang berjumlah 90 orang dari tiga kelas. Sampel ditentukan dengan teknik purposive sampling sehingga diperoleh 2 kelas sebagai kelas eksperimen dan kelas kontrol. Desain penelitian adalah eksperimen semu. Instrumen yang digunakan adalah tes menulis drama. Data yang terkumpul dianalisis menggunakan analisis deskriptif dan analisis inferensial berupa independent t-test. Hasil penelitian menunjukkan bahwa kelompok yang menggunakan media audiovisual memperoleh hasil yang lebih baik dibandingkan media audio. Hasil penelitian tersebut dibutikan dengan uji-t yang menunjukkan bahwa media audiovisual efektif digunakan dalam pembelajaran menulis naskah drama. Implikasi penelitian ini adalah guru dapat meningkatkan kemampuan siswa menulis naskah drama bahasa Indonesia dengan menggunakan media audiovisual.